Risco e impactos de poluição nas águas subterrâneas pelo uso e ocupação do solo no Porto das Dunas - Aquiraz/CE - Araújo, Karen Vendramini de (2014)
This work was performed at Porto das Dunas, in the city of Aquiraz, aiming to assess the risk and impacts of pollution in groundwater, resulting from the use and occupation of area. The methodology consisted of a literature search, preparation of records of wells and thematic bases, updating the register of pre-existing wells, obtaining data for pH, total dissolved solids (TDS) and electrical conductivity (EC) in 32 wells, collecting 15 samples for physicochemical and bacteriological analysis and processing and data integration. Porto das Dunas has an intense tourism, being densely occupied by homes, hotels, resorts and tourist developments. However, the area does not have a water supply and sewerage system, being fully supplied by groundwater and the disposal of sewage accomplished through septic cesspools. The Dunes Aquifer is the most important in the area of research both in occurrence (90%) and in water potential. Based on the methodology GOD, the Dunes Aquifer in the area of research, has medium to high vulnerability. The vulnerability of the Dunes Aquifer associated with a constant contaminant load from septic cesspools existing in the area is a high risk of groundwater pollution from Porto das Dunas. The impacts of the use and occupation were assessed using qualitative study of groundwater in the area of research performed based on the parameters of pH, total dissolved solids (TDS) and electrical conductivity (EC) from the field and physicochemical and bacteriological analyzes. It was found that concentrations of pH, TDS and EC are within recommended by Ordinance nº 2914/2011 MS standards. Have the 15 physicochemical analyzes showed concentrations of hardness, turbidity, fluoride, sodium nitrite within the potability standards and concentrations of chloride (1 sample), iron (2 samples) and nitrate (1 sample) out of potability standards. In the microbiological quality of water, it was found that 94% of the samples showed total or fecal coliforms. The presence of coliforms indicates contamination in groundwater arising from existing domestic cesspools in the area.